1995
DOI: 10.1007/bf01590946
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the identification of the pathogens of bacterial meningitis by the polymerase chain reaction

Abstract: A combination of universal and species-specific primers was used to detect and differentiate by nested polymerase chain reaction (PCR) the four species most commonly causing bacterial meningitis. Primers recognising conserved sequences in the 16S and 23S ribosomal RNA genes were employed to amplify the 16S-23S spacer region from Neisseria meningitidis, Haemophilus influenzae (type b), Streptococcus pneumoniae, and Streptococcus agalactiae (group B streptococcus). The sequence of the most abundant spacer produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…Previous studies assessing the use of PCR-based strategies for the diagnosis of meningococcal meningitis in blood and CSF [e.g., 3, 5±8] have resolved the PCR ampli®cation products on agarose gels [5] or have relied on detection and identi®cation by ELISA [3] or DNA sequencing [7,8]. The present study investigated the possibility of making the PCR technique more accessible to routine diagnostic laboratories by the use of a simple and cheap immunoassay device for detection of PCR products.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessing the use of PCR-based strategies for the diagnosis of meningococcal meningitis in blood and CSF [e.g., 3, 5±8] have resolved the PCR ampli®cation products on agarose gels [5] or have relied on detection and identi®cation by ELISA [3] or DNA sequencing [7,8]. The present study investigated the possibility of making the PCR technique more accessible to routine diagnostic laboratories by the use of a simple and cheap immunoassay device for detection of PCR products.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the usefulness of eubacterial broad-range PCRs for the diagnosis of bacterial meningitis (3,6,13,14,23). However, most published PCR protocols were either time-consuming or did not facilitate species diagnosis of the bacterial pathogens.…”
mentioning
confidence: 99%
“…Varying degrees of success have been realized using PCR-based assays for detecting S. pneumoniae with primers specific to repetitive regions or to genes encoding rRNA (7,9,12), pneumolysin (18,19,23), or autolysin (5,14,18). Autolysin and pneumolysin, which are encoded by the lytA and ply genes, respectively, represent potential targets for the specific detection of S. pneumoniae.…”
mentioning
confidence: 99%